Do the effects of parent-based alcohol interventions depend on college residence? A short communication. (June 2022) - LaBrie, Joseph W.; Trager, Bradley M.; Morgan, Reed M.; Boyle, Sarah C.; Taylor, J. Eason; Turrisi, Robert
Abstract: Parent-based interventions (PBIs) and living at home with one's parents both have been shown to mitigate alcohol risk associated with the first year of college. The current study extends these findings by examining the independent and interactive effects of these two constructs on first-year drinking. The sample included 82 parent-student dyads. Parents were randomized to receive an online PBI that either did (intervention; n = 44) or did not ( n = 38) include alcohol-related content in December 2020. Students completed online surveys assessing college residence and drinking (typical weekly and peak) in August 2020 (T1) and February 2021 (T2). Hierarchical zero-inflated Poisson models assessed the main and interaction effects of having a parent in the intervention group (vs control) and living with parents (vs without) on drinking outcomes, controlling for T1 alcohol use. Results revealed that living with parents predicted decreases in typical weekly drinking and having a parent in the intervention predicted decreases in the number of drinks consumed on one's peak drinking occasion at T2. Treatment*residence was also significantly associated with typical weekly drinking in the inflated model. These results suggest that moving out was associated with a greater likelihood of not drinking during a typical week if students had a parent in the intervention and a lower likelihood of not drinking during a typical week if they had a parent in the control application. Together, findings support continued exploration of this online PBI as it appears to reduce peak drinking during the first year of college and reduces the odds of students drinking during a typical week when they move out of their parents' home.